The law and economics of intermediaries of personal information - Giacomo Luchetta (International Telecommunications Society (ITS), 2013)
This paper explores a class of firms: the intermediaries of personal information. In the economics of personal information, scarcity is no longer the only, and foremost, determinant of value. The most important determinant of value becomes connection. Adapting what Gervais claims to be the first law of an information-flooded cloud-modelled economy, value is not derived from scarcity but rather from the fact that those who value it most will find it. Personal information is the raw material to create connections. Intermediaries collect personal information in exchange for goods or services, regardless of whether they actually need that information to perform their main activity, and use this information to connect other goods and services with the users who value them most, e.g. via personalisation or targeted advertising. Many firms in many different sectors are, or could become, intermediaries of personal information, from Google to supermarkets, from telecom operators to insurance companies. The descriptive analysis of this industry has consequences in terms of business model and regulatory approach. As for the former, it is worth exploring the conditions for which a firm could profitably become an intermediary of personal information and thereby exploit untapped resources for revenue generation. As for the latter, an imperfect understanding of the economics of personal information creates the risk for misaligned norms, and therefore for an uneven competition.
Keywords: 330